640. Analytical Validation of the BioFire® Bone and Joint Infection (BJI) Panel for the Identification of Bacteria, Yeast, and Antimicrobial Resistance Genes from Synovial Fluid. (31st December 2020) - Francis, Nicholas; Barbier, Laurence; Dubost, Caroline; Billet, Elodie; Manwaring, Joel; Southwick, Josh; Dawson, Tyson; Gann, Jess; Ekins, Kevin; Arce, Jennifer; Flaherty, Briana; Durand, Harmonie; et al.
Abstract: Background: The BioFire Bone and Joint Infection (BJI) Panel is a sample-to-answer test for the qualitative detection of nearly 40 different bacteria, yeast, and antimicrobial resistance (AMR) genes in synovial fluid (SF). The panel aims to improve on current culture-based diagnostics, particularly for detection of anaerobes (e.g. Finegoldia magna, Kingella kingae, Cutibacterium, Anaerococcus and Peptoniphilus species, and others) in about an hour. Analytical performance of the panel (Limit of Detection (LoD), analytical reactivity and specificity, interference, reproducibility), and specimen storage conditions are described. Methods: LoD for each analyte was estimated from serial dilutions and confirmed at the lowest titer with ≥95% detection. A collection of >350 isolates representing genetic and geographic diversity of analytes was tested near LoD to assess analytical reactivity, and more than 420 near-neighbor, commensal, pathogenic, or environmental off-panel species were evaluated for assay specificity. Reproducibility was evaluated in a multi-laboratory multi-variable study, and the impact of storage and potentially interfering substances on the accuracy of test results was also assessed. Testing was performed with Investigational Use Only kits. Results: The confirmed LoD for bacteria and yeast ranged from 100 - 10, 000 CFU/mL. Sequence analysis and testing demonstrated clinically appropriate specificity and reactivity with a variety of isolates and different AMR gene types. Accurate and reproducible organism and AMR gene detection was observed with repeated testing of samples over several days (99.9% agreement with the expected results), and detection was not affected by potentially interfering substances nor by refrigerated sample storage. Conclusion: The BioFire BJI Panel is a robust, accurate, and easy-to-use multiplex PCR test capable of detecting many aerobic and anaerobic bacteria, yeast, and AMR genes in synovial fluid specimens. Rapid and reliable molecular detection of possible BJI pathogens may advance the diagnosis and effective management of bone and joint infections. Note: This panel has not been evaluated by the FDA or other regulatory agencies for diagnostic use. Disclosures: Nicholas Francis, n/a, BioFire Diagnostics (Employee) Laurence Barbier, n/a, Biomerieux (Employee) Caroline Dubost, n/a, Biomerieux (Employee) Elodie Billet, n/a, Biomerieux (Employee) Joel Manwaring, n/a, BioFire Diagnostics (Employee) Josh Southwick, n/a, BioFire Diagnostics (Employee) Tyson Dawson, n/a, BioFire Diagnostics (Employee) Jess Gann, n/a, BioFire Diagnostics (Employee) Kevin Ekins, n/a, BioFire Diagnostics (Employee) Jennifer Arce, MS, BioFire Diagnostics/BioMerieux (Employee) Briana Flaherty, n/a, BioFire Diagnostics (Employee) Harmonie Durand, n/a, Biomerieux (Employee) Chris Cantrell, n/a, Biomerieux (Employee) Elizabeth Amiott, n/a, BioFire Diagnostics (Employee)